Assessment of Ground water Quality for Drinking purpose in the Shaqlawa Area, Erbil-KRI - Siraj M. A. Goran; Dilshad A. Rasul; Dldar S. Ismaeel (Zanco Journal of Pure and Applied Sciences, 2021)
Physical, chemical and biological properties of some artesian wells in Shaqlawa area were done, through collecting water samples for 12 artesian wells seasonally (Spring, summer, autumn and winter) during 2016, which distributed in Shaqlawa, Harir and Permam area. In ground water samples of study areas, electric conductivity was range between 252-2300 µS/cm, with mean values for all 12 wells were range between 474.8-1575.5 and overall mean was 689.3.The pH of study samples is neutral or around neutrality and ranged between 7.0 and 8.4 With mean values ranged between 7.2-8.2 and the overall mean 7.6 and standard deviation of 0.4 and agreed with WHO guidelines for drinking water purpose. Sodium and potassium levels were ranged from 1 to 310 and 0.1 to 8.18 mg/L. Turbidity is one of the parameters for the acceptability of drinking water quality. WHO, guidelines for turbidity is < 5 NTU. The overall mean value of total alkalinity in studied water samples was 278.5 mg CaCO3/L. The levels of sulfate in groundwater samples of the study area ranged between 11.8 to 314 mg/L. The overall mean and STDEV is 72.7 and 71.6 respectively. . Concentration of total hardness in the studied area were ranged between 160 and 560 mg CaCO3/L. Furthermore, calcium dominated magnesium in studied well water. Nitrate levels in groundwater samples were low. Microbiological analysis of studied water samples was zero, except in two samples. Water quality index or studied parameters in groundwater samples were excellent.